Feasibility and beneficial effects of an early goal directed therapy after cardiac arrest: evaluation by conductance method - Ole Broch (Nature Portfolio, 2021)
Abstract Although beneficial effects of an early goal directed therapy (EGDT) after cardiac arrest and successful return of spontaneous circulation (ROSC) have been described, clinical implementation in this period seems rather difficult. The aim of the present study was to investigate the feasibility and the impact of EGDT on myocardial damage and function after cardiac resuscitation. A translational pig model which has been carefully adapted to the clinical setting was employed. After 8 min of cardiac arrest and successful ROSC, pigs were randomized to receive either EGDT (EGDT group) or therapy by random computer-controlled hemodynamic thresholds (noEGDT group). Therapeutic algorithms included blood gas analysis, conductance catheter method, thermodilution cardiac output and transesophageal echocardiography. Twenty-one animals achieved successful ROSC of which 13 pigs survived the whole experimental period and could be included into final analysis. cTnT and LDH concentrations were lower in the EGDT group without reaching statistical significance. Comparison of lactate concentrations between 1 and 8 h after ROSC exhibited a decrease to nearly baseline levels within the EGDT group (1 h vs 8 h: 7.9 vs. 1.7 mmol/l, P < 0.01), while in the noEGDT group lactate concentrations did not significantly decrease. The EGDT group revealed a higher initial need for fluids (P < 0.05) and less epinephrine administration (P < 0.05) post ROSC. Conductance method determined significant higher values for preload recruitable stroke work, ejection fraction and maximum rate of pressure change in the ventricle for the EGDT group. EGDT after cardiac arrest is associated with a significant decrease of lactate levels to nearly baseline and is able to improve systolic myocardial function. Although the results of our study suggest that implementation of an EGDT algorithm for post cardiac arrest care seems feasible, the impact and implementation of EGDT algorithms after cardiac arrest need to be further investigated.